The Observation Hive Handbook : Studying Honey Bees at Home - Linton, Frank, 1945- (Book collections on Project MUSE., 2017)
This book will guide you in selecting an observation hive and choosing a site for it, modifying the hive and the site as needed, installing the hive, working with the hive, and maintaining the hive. It will prepare you to take a temporary portable observation hive to a market, fair, or school. Most important, it describes and illustrates the many ways you can use your observation hive to learn more about honey bees and how to care for them.